Особливості розвитку видів-інтродуцентів у штучно створених трав’янистих угрупованнях рослин - Kabanov, A.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
The results of study of introduced species dynamics in artificial communities under the conditions of their autonomous development are given. The peculiarities of structure and content of artificial communities are considered.